ANALYSIS OF THE DEVELOPMENT STRATEGY FOR PAAL BEACH BY THE LOCAL GOVERNMENT OF MINAHASA UTARA REGENCY - Cynthia Febri Sri Indarti; Matthew Miracle Rawung (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2026)
Paal Beach, located in North Minahasa Regency, is a marine tourism destination renowned for its natural underwater beauty and tranquil seascape. Despite its ecological and economic potential, the management of this tourism site-under the supervision of the North Minahasa Department of Tourism and Culture- has yet to reach an optimal level, as indicated by a decline in tourist visits and the lack of development prioritization. This study aims to analyze development strategies for Paal Beach and to identify priority issues in its sustainable tourism development. Employing a pragmatism paradigm, the research adopts a mixed-methods approach, integrating qualitative techniques (observation, in-depth interviews, and document analysis) with quantitative analysis (expert-validated questionnaires). The analytical framework combines SWOT analysis with the Analytical Hierarchy Process (AHP), facilitated by Expert Choice software, to assess strategic priorities systematically. Key informants include local government officials, tourism managers, and visitors. The findings reveal four main strategic issues: (1) the absence of a structured development strategy, (2) limited involvement of local stakeholders such as Tourism Awareness Groups (POKDARWIS), Village-Owned Enterprises (BUMDes), and village governments, (3) low public awareness of tourism, and (4) underutilization of local economic potential. The study concludes that the formulation of a structured development strategy is the most urgent priority, followed by enhanced participation of local stakeholders to ensure inclusive and sustainable tourism governance